Local calibration of the Hirsch model to determine the degree of blending between aged and virgin asphalt binders. Issue 9 (2nd September 2022) - Zokaei Ashtiani, Milad; Mogawer, Walaa S.; Tabatabaee, Nader
Abstract : Aged asphalt binder in reclaimed asphalt pavement (RAP) or recycled asphalt shingles (RAS) blends only partially with the virgin binder. To better understand this state of blending, the asphalt mixtures in this study were designed, mixed, and compacted using different RAP and RAS contents. The asphalt binders were extracted and recovered from RAP and RAS and then blended with different proportions of a virgin binder. The master curves for the asphalt mixtures and asphalt binder blends were then constructed from the measured data. A locally calibrated Hirsch model was developed to estimate master curves for the asphalt mixtures from the corresponding binder-blend data. Pairwise comparison of the master curves for RAP and RAS and virgin binder showed that degree of blending occurred at 50% to 60% for RAP and at 15% to 30% for RAS.